Perspectives of Academics, Teachers, and Pre-Service Teachers on the Establishment of National Education Academies - Aysel Arslan; Mevlüde Sümeyye Polat (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to examine the perspectives of academics, teachers, and pre-service teachers regarding the establishment of National Education Academies and their potential role within the teacher education system. The research focuses on how these academies are expected to contribute to teacher preparation, the similarities and differences between National Education Academies and Faculties of Education, and their possible impact on the professional competencies of pre-service teachers. A qualitative research approach was adopted using a phenomenological design. Data were collected through semi-structured interviews with eight academics, thirteen teachers, and ten pre-service teachers. The collected data were analyzed using content analysis to identify recurring themes, sub-themes, and patterns across participant groups. The findings indicate that stakeholder perspectives differ considerably. Academics generally view the National Education Academies as potentially beneficial, particularly if structured around a practice-based and field-oriented training model. They emphasize the importance of integrating theory and practice, strengthening technological infrastructure, and ensuring transparency and merit-based implementation. In contrast, some teachers and pre-service teachers express concerns that the academies may duplicate existing curricula and undermine the institutional role of Faculties of Education. Pre-service teachers, in particular, tend to perceive the academy model as repetitive, time-consuming, and potentially demotivating. Overall, the study suggests that for National Education Academies to effectively support teacher education, they must adopt an innovative, holistic, and collaborative approach that complements rather than competes with existing university-based teacher education structures.